Tensile behaviors of friction bolt connection with bolt head corrosion damage: Experimental research B. (January 2016) - Kim, In-Tae; Lee, Jae Min; Huh, Jungwon; Ahn, Jin-Hee
Abstract: In this study, the tensile characteristics of a friction connection using a high-strength bolt, based on the clamping force loss developed by sectional corrosion damage to the bolt head, was examined. Eighteen specimens with bolt connections were tested to evaluate the tensile strength. In these test specimens, artificial corrosion damage was introduced to the bolt head of the bolt connection, creating a clamping force loss. In the tensile strength tests, the tensile failures of connected steel plates were observed; the tensile strength was unaffected by the artificial sectional corrosion damage to the bolt head for this failure mode. However, the friction resistance of the specimens was affected by the clamping force of the bolt, and thus, their friction loads were slightly reduced depending on the sectional damage level of the bolt head. From the friction load–clamping force relationship, friction-resistance equations were used to approximate the friction resistance of the friction bolt connection. Highlights: Tensile strength test for bolt connection with the corrosion damage of the bolt head Measuring initial friction load and tensile strength depending on the corrosion damage of the bolt head Examining relationship between friction load and clamping force affected by corrosion damage of bolt head